Endolymphatic Sac Tumour: A Case Report and Review of the Literature - Patankar, Amey P.; Aiyer, Ranjan; Chamarajan, Srinivasan; Vala, Nidhi (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2021)
Introduction Endolymphatic sac tumor (ELST) is a slow-growing, low-grade, locally-infiltrative tumor arising from the endolymphatic sac/duct, which is located in the posterior part of the petrous temporal bone. It may be sporadic in origin, or may be associated with Von-Hippel Lindau (VHL) syndrome.Case description A 40-year-old female patient with an ELST without VHL syndrome who was treated successfully by microsurgical extirpation of the tumor.Discussion We discuss the radiological features and the histopathology of this rare tumor and review the relevant literature.Conclusion The case herein reported adds to the previously-reported cases of this rare tumor.
Keywords: endolymphatic sac tumor; temporal bone tumors; Von-Hippel Lindau syndrome